2020
DOI: 10.1038/s41467-020-17308-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of catalytic ribonucleoprotein complex RNase MRP

Abstract: RNase MRP is an essential eukaryotic ribonucleoprotein complex involved in the maturation of rRNA and the regulation of the cell cycle. RNase MRP is related to the ribozyme-based RNase P, but it has evolved to have distinct cellular roles. We report a cryo-EM structure of the S. cerevisiae RNase MRP holoenzyme solved to 3.0 Å. We describe the structure of this 450 kDa complex, interactions between its components, and the organization of its catalytic RNA. We show that some of the RNase M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
1
35
0
1
Order By: Relevance
“…As the control, we used the endogenously expressed human ribonuclease mitochondrial RNA processing (RMRP) RNA and purified both SARS-CoV-2 RNA and RMRP from infected Huh7 cells. RMRP was selected for several reasons: (1) RMRP interacts with approximately ten well-known proteins that serve as an internal control 15 , 23 ; (2) RMRP is not translated; and (3) RMRP does not globally bind to mRNA. Hence, RMRP-binding proteins are distinct from the group of proteins expected to bind to SARS-CoV-2 RNAs, making it an ideal control for the discovery of unknown interactors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the control, we used the endogenously expressed human ribonuclease mitochondrial RNA processing (RMRP) RNA and purified both SARS-CoV-2 RNA and RMRP from infected Huh7 cells. RMRP was selected for several reasons: (1) RMRP interacts with approximately ten well-known proteins that serve as an internal control 15 , 23 ; (2) RMRP is not translated; and (3) RMRP does not globally bind to mRNA. Hence, RMRP-binding proteins are distinct from the group of proteins expected to bind to SARS-CoV-2 RNAs, making it an ideal control for the discovery of unknown interactors.…”
Section: Resultsmentioning
confidence: 99%
“…As the control, we used the endogenously expressed human ribonuclease mitochondrial RNA processing (RMRP) RNA and purified both SARS-CoV-2 RNA and RMRP from infected Huh7 cells. RMRP was selected for several reasons: (1) RMRP interacts with approximately ten well-known proteins that serve as an internal control 15,23 ; (2) RMRP is not translated; and (3) RMRP does Adjusted P value CNBP NSP6 N S LARP4 STIP1 PUM1 YBX1 YBX3 NSP15 PABPC4 SYNCRIP G3BP2 YTHDF2 ORF3a RTCB PABPC1 SND1 M EIF4B UPF1 EIF4H MOV10 CSDE1 A1CF RBMS2 RAB6A RAB6D PPP1CC RPS2 SCFD1 NSP12 CAPRIN1 DDX3X EIF3E RPS14 NSP16 RPS10 RPL15 LSM14A HNRNPA1 IGF2BP2 LIN28B RYDEN STRAP NSP9 ACTR2 ANXA1 USO1 RPL6 CFL1 DDX1 HDLBP EIF5A PPP1CB RPL13 RPS3…”
mentioning
confidence: 99%
“…The results demonstrate that the 5.8S L processed from the ∆2 pre-rRNA is incorporated into 60S and 80S ribosomes as well as polysomes (Figure 8A, lanes 14-19 and lanes 21-27, respectively). Additionally, probing with O552 showed that the 5 -extended 5.8S RNA transcripts ("exoladders") were also incorporated into ribosomes, including polysomes (Figure 8A, lanes [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. In other words, the extensions did not preclude incorporation of the 5.8S-containing rRNA into functional ribosomes.…”
Section: 8s Rrna With 5 Extended Ends Are Incorporated Into Functional Ribosomesmentioning
confidence: 98%
“…It should be noted that, even though 8 nucleotides around the A3 consensus sequence contact the RNase MRP binding pocket, only two nucleotides in the consensus sequence have a strong effect on the rate of cleavage [46][47][48]. Thus, we cannot exclude ectopic RNase MRP cleavage of ∆14, ∆15, and ∆16 in the RRP2 strain, although if this were the case, we would have expected that such misplaced cleavage should also suppress the effect of the inhibition of A3 cleavage in the ∆18 mutant.…”
Section: The Rnase Mrp-induced Switch Between 58s L and 58s S Production Not Due To Changes In A3 Cleavagementioning
confidence: 99%
“…It should be noted, however, that even though 8 nucleotides around the A3 consensus sequence contact the RNase MRP binding pocket, only two nucleotides in the consensus sequence have a strong effect on the rate of cleavage [38,39,41]. Thus, we cannot exclude ectopic RNase MRP cleavage of ∆14, ∆15, and ∆16 in the RRP2 strain, although if this were the case, we would have expected that such ectopic cleavage should also suppress the effect of the inhibition of A3 cleavage in the ∆18 mutant.…”
Section: Switching Between the Pathways To The 5' End Of 58s Rrnamentioning
confidence: 99%